Evaluating the effectiveness of chemotherapy for thymic epithelial tumors using the CD‐DST method - Lei Yu; Bao‐xun Zhang; Xin Du; Zhen Yu; Xing‐guo Yang; Yu‐xuan Jiang (Thoracic Cancer, 2020)
Background Thymic epithelial tumors (TET) are frequently eligible for curative‐intent surgical resection. For locally advanced TETs, chemotherapy has been used to both reduce the tumor burden and achieve prolonged disease control. However, effective therapy for this disease largely remains to be determined. Here, we report the chemosensitivity of 100 patients with TETs determined by the collagen gel droplet embedded culture‐drug sensitivity test (CD‐DST). Methods A total of 100 patients with TETs underwent surgical resection. The efficacy of antitumor agents on TET cells was tested by CD‐DST. Results Thymic epithelial tumors were pathologically confirmed after surgery: two cases were type A thymoma, 17 were type AB, 12 were type B1, 44 were type B2, 12 were type B3, and there were 13 cases with thymic carcinoma. A total of 36% patients with TETs were sensitive to different types of chemotherapeutic agents. There was no significant differences in age, histological type, clinical staging, or association with autoimmune diseases between sensitive and nonsensitive cases. Type B1 and B2 thymoma were relatively more sensitive to chemotherapeutic agents (6/12 and 18/44, respectively), while sensitivity of type B3 cases to chemotherapeutic agents was much lower (only 2/12). Cases with type A thymoma were not sensitive to any antitumor drugs. Among 11 chemotherapeutic agents tested in our study, the sensitivity of TETs to EPI was the highest (16%). No patients with thymoma were sensitive to Alimta (Pemetrexed). Conclusions Our work illuminates the effectiveness of chemotherapy for TETs and provides important clues for choosing antitumor drugs with relatively high drug sensitivity to TETs in advance.